Partial Purification, Characterization, and Application of Extracellular Aspartic Protease from Lactobacillus casei WSP in Producing the Bioactive Peptides with Antibacterial and Antioxidant Activity - Solikhin, Akhmad; Mustopa, Apon Zaenal; Suharsono, Suharsono; Putranto, Wendry Setiyadi (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2018)
Lactobacillus casei WSP-derived an aspartic protease was sequentially purified by using chromatography gel filtration sephadex G-50. It resulted in a 22.81-fold increase of specific activity (51.5 U/mg) with a final yield of 1.9%. The estimated molecular weight of the purified enzyme was 37 kDa and showed gelatinolytic activity in zymogram assay. The enzyme exhibited optimum activity at 40ºC and pH 6 with casein as the substrate. Enzyme activity was significantly inhibited by pepstatin A (0.5 mM and 1 mM), confirming that this enzyme is a group of aspartic proteases, while other inhibitors such as EDTA, PMSF and iodoacetic acid showed no inhibition effect on the activity of enzyme. The addition of metal ion to the enzyme decreased enzyme activity, indicating the proteolytic enzyme was metal ion- dependent. Denaturant such as DDT tended to increase caseinolytic activity. Furthermore, this enzyme was capable of generating the new peptides from skimmed milk with the size 8 kDa, 10 kDa and 15 kDa. These peptides have potential as antibacterial and antioxidant agents.